Some final words - Starn, Orin (1992)
I never imagined that this article would provoke so much outrage and anger. I wrote it in 1989 as a serious and honest attempt to address what seemed to me to be some significant problems in the way many anthropologists had conceived of the Andean peasant experience. In this short intervention I would like to respond to the commentators and offer some final thoughts on the debate.